2011
DOI: 10.3109/00365521.2011.639078
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of clinical prediction rules in peptic ulcer perforation: an observational study

Abstract: The Boey score, the ASA score, the APACHE II score, and the sepsis score predict mortality poorly in patients with PPU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 41 publications
6
34
2
Order By: Relevance
“…There are various studies in the literature regarding mortality prediction by the APACHE II score (13,32,36). In our study, we identified that patients who had an APACHE II score above 11 had a significantly higher mortality.…”
Section: Discussionsupporting
confidence: 59%
“…There are various studies in the literature regarding mortality prediction by the APACHE II score (13,32,36). In our study, we identified that patients who had an APACHE II score above 11 had a significantly higher mortality.…”
Section: Discussionsupporting
confidence: 59%
“…However, prediction values of Boey scoring system were quite varying in several studies as AUC values ranged between 0, 63 to 0, 86 [5,11,12,15,24]. In our analysis we found a better Boey value (AUC: 0.92) for prediction then the reported ones.…”
Section: Discussionmentioning
confidence: 41%
“…[6,11,12,5] Buck and colleagues on the other hand expressed the meagre ability of Boey score in predicting mortality and morbidity status. [13] Their multicentre study also stated that the ASA score, and sepsis score were not able to provide convincing results in prognostication of patients. [13] Presence of comorbidities which are divergent per patient combined with increasing patient age not only makes diagnostic decisions operose but also further delays operation time thus adding on to mortality than death due to PPU in itself.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Their multicentre study also stated that the ASA score, and sepsis score were not able to provide convincing results in prognostication of patients. [13] Presence of comorbidities which are divergent per patient combined with increasing patient age not only makes diagnostic decisions operose but also further delays operation time thus adding on to mortality than death due to PPU in itself. [14] Metabolic acidosis, malnutrition, hypoalbuminaemia, smoking, female gender are essential isolated risk factors in development of mortality due to PPU.…”
Section: Discussionmentioning
confidence: 99%